Aerodynamic and heat transfer performances of a highly loaded transonic turbine rotor with upstream generic rim seal cavity - Zakaria Mansouri (Propulsion and Power Research, 2021)
In turbine disk cavity, rim seals are fitted between the stator and its adjacent rotor disk. A coolant air injected through the turbine disk cavity to prevent the ingress of mainstream hot gases. The purpose of this paper is to investigate numerically the effect of the upstream purge flow on the aero and thermal performances of a high pressure turbine rotor. The investigations are conducted on a generic rim seal cavity inspired from a realistic turbofan engine. Four purge fractions (PF) equal to 0.2%, 0.5%, 1.0% and 1.5% of the mainstream are considered. The simulations are done by solving the three-dimensional Reynolds averaged Navier-Stokes and energy transport equations. The results include the effect of the PF on the cooling effectiveness, the sealing effectiveness, the secondary flows with losses and the heat transfer behavior, within the cavity and across the rotor passage. The low PF of 0.2% provided a low cooling effectiveness, a moderate sealing effectiveness and minimum losses. The high PF of 1.5% gave a high cooling effectiveness, a best sealing effectiveness and maximum losses. The medium PF of 1.0% supplied a compromise between the aerodynamic and thermal design needs with good cooling and sealing efficiencies and a tolerable level of losses.